The Relationship Between Mothers' Anxiety Levels and Hb-0 Vaccination among Infants in Kota Datar Village - Yulia Safitri; Nurhaida Br Kaban; Nopita Yanti Sitorus; Pratiwi Syah Putri (Universitas Islam Negeri Sumatera Utara, Medan, 2026)
Timely administration of the hepatitis B vaccine at birth (HB-0) is crucial to prevent mother-to-child transmission of the hepatitis B virus. However, HB-0 vaccination coverage, both globally and locally, remains below the desired level. Maternal concerns have been suggested as a potential barrier to newborn vaccination. This study aimed to evaluate the relationship between maternal anxiety levels and the use of HB-0 vaccination in infants in Kota Datar Village, located in Hamparan Perak District, Deli Serdang. In January and February 2024, a cross-sectional survey was conducted involving all mothers with infants aged 0–7 days (n = 35). Maternal anxiety was measured using the 20-item Zung Anxiety Scale. HB-0 vaccine acceptance was documented based on maternal statements and local government records. Chi-square analysis was used to test the relationship, with a significance level of α = 0.05. The group of 35 participants consisted mostly of people aged 20–35 years, and all had completed high school education. HB-0 was administered to 37.1% of infants (13 of 35). Conversely, 62.9% (22 of 35) did not receive HB-0 within the specified birth period. Maternal anxiety was a common problem, affecting 25 of 35 women. Mothers with severe anxiety were significantly less likely to administer HB-0 than those with mild anxiety (χ², p = 0.002). Survey responses, which included quantitative data, showed that safety concerns, fear of fever after vaccination, and misinformation were common reasons for concern. In this group, a significant association was found between maternal anxiety and reduced HB-0 acceptance. To improve the timely immunization of newborns against hepatitis B, it is recommended to use interventions that include prenatal counseling, focused information about risks, and increased involvement of frontline health workers. Future research should investigate the extent to which interventions to reduce anxiety affect vaccine acceptance. Keywords: Hepatitis B Birth Dose, HB-0 Immunization, Maternal Anxiety, Vaccine Uptake, Newborn Immunization.